SnRK1 Kinase and the NAC Transcription Factor SOG1 Are Components of a Novel Signaling Pathway Mediating the Low Energy Response Triggered by ATP Depletion - Hamasaki, Hidefumi; Kurihara, Yukio; Kuromori, Takashi; Kusano, Hiroaki; Nagata, Noriko; Yamamoto, Yoshiharu Y.; Shimada, Hiroaki; Matsui, Minami (Frontiers in Plant Science, 2019)
Plant growth is strictly controlled by cell division, elongation and differentiation for which adequate supplies of intracellular ATP are required. However, it is unclear how changes in the level of intracellular ATP affect the growth response. To reveal the specific pathway dependent on ATP concentration, we performed analyses on the Arabidopsis mitochondria mutation sd3. The mutant is tiny, a result of a low amount of ATP caused by the disruption of Tim21, a subunit of the TIM23 protein complex localized in the inner membrane of the mitochondria. Loss of function of suppressor of gamma response 1 (SOG1) also restored the dwarf phenotype of wild type treated with antimycin A, a blocker of ATP synthesis in mitochondria. The sd3 phenotype is partially restored by the introduction of sog1, suppressor of gamma response 1 and kin10/kin11, subunits of Snf1-related kinase 1 (SnRK1). Additionally, SOG1 interacted with SnRK1, and was modified by phosphorylation in planta only after treatment with antimycin A. Transcripts of several negative regulators of the endocycle were up-regulated in the sd3 mutant, and this high expression was not observed in sd3sog1 and sd3kin11. We suggest that there is a novel regulatory mechanism for the control of plant development involving SnRK1 and SOG1, which is induced by low amounts of intracellular ATP, and controls plant development.